PERBEDAAN KANDUNGAN MAKRONUTRIEN (LEMAK, PROTEIN, KARBOHIDRAT) DALAM SANTAN MURNI DAN SANTAN TAMBAHAN AIR KELAPA TUA - Febriniwati Rifdi; Siska Zhulhida (Maternal Child Health Care, 2021)
Coconut milk is a source of fat and has high enough calories. Coconut milk has other content, namely carbohydrates and protein. This study aims to determine Analysis on the Differences of Macronutrient Content (Protein, Fat, Carbohydrates) in Pure Coconut Milk (Coconut Milk) and Coconut Milk (Coconut Milk) with Coconut Water addition. The type of this study was a laboratory experiment by analyzing the levels of macronutrients in pure coconut milk and coconut milk with the addition of old coconut water. It was carried out at the BARISTAND Padang Laboratory on November-December 2020 and the objects in this study were pure coconut milk and coconut milk with old coconut water squeezed. The results showed that the highest carbohydrate content in pure coconut milk was 1.53% while the lowest carbohydrate was found in coconut milk with aged coconut water was 1.51%. The highest fat content in pure coconut milk was 35.3% while the lowest fat found in coconut milk with old coconut water as much as 31.8%. The highest protein content in pure coconut milk was 3.46% while the lowest carbohydrate was found in coconut milk with aged coconut water was1.92%. Based on the results of this study, pure coconut milk and coconut milk with treatment are recommended to be good complementary drinks for breast milk in terms of micronutrients. This study suggests that people can use coconut milk as a complementary drink to meet their daily nutritional needs